Quantitative Risk Analysis: Storeroom of explosives used in the process of cannonading of an oil well - Jeronimo, Carlos Enrique de Medeiros; Mendonça, Leonardo Vinícius Lopes de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The present study aims to conduct a quantitative analysis of the risks present in the storage of explosive charges used in the cannonade process technique used in oil well completion process, which aims to clear and effective communication between the well and the formation. This case refers to the perforation of the coating, cement and training by explosive charges. By means of different scenarios can be quantified by means of probit risks arising in storerooms and radioactive explosive charges used in the cannonade service, sizing the areas of vulnerability and risks associated with the activity method. Data were collected and used to quantify the risks of each scenario, where by the results can be interpreted and show how working radius relative to the bunkers are achieved if some event occurs. The results obtained from the study showed the impact that an accident involving explosive charges would cause onsite and in your neighborhood. With knowledge of the total amount of explosive present in the magazine, one can quantify the minimum distance achieved due to the scenarios studied.